Propuesta didáctica para el desarrollo del Pensamiento Computacional mediante la programación visual por bloques. - Ortiz Yumisaca, Andrea Elizabeth (2024)
This research aims to develop a didactic proposal to support the enhancement of Computational Thinking through block-based visual programming. The study, characterized as applied, commenced with a thorough literature review and analysis of the syllabus employed in the Computational Thinking Development course during the academic periods of 2023-1S and 2023-2S. This course is part of the curriculum in the first semester of the Pedagogy of Experimental Computer Science program at the National University of Chimborazo, Ecuador. A didactic guide was successfully crafted by applying the ADDIE instructional design model and following the steps proposed by Arteaga & Figueroa (2004). This guide incorporates content and activities aimed at creating simple yet practical applications using the PictoBlox programming environment. A pilot test of the didactic guide was conducted, revealing a notable interest among first-semester students in the program above, most expressed satisfaction with the instructional guide.